Os fundos de investimentos na América Latina: Argentina, Brasil, Chile, México e Peru (1995-2004) - Jesus, Marcelo de (2005)
The purpose of this study is to analyze the evolution of the mutual funds as one of the main institutional investors in Latin America, with the analysis of five countries in this region: Argentina, Brazil, Chile, Mexico and Peru, in the period between 1995 to 2004. The analysis is performed starting from the middle 1990´s, when the growth of the mutual funds assets got stronger and made such institutions to become an important money saving mechanism. It is discussed its role in the financial system, also the factors which influence objective to surpass the old restriction to the financing investment. The origin of the mutual funds is briefly described, starting the discussion about the reasons that contributed to the institutionalization of the money savings and the function attributed by the Keynesian and post-Keynesian theoretical reference to the institutional investors. Furthermore, it looks for identifying how regulation evolved. At last, it is done an analysis of the evolution of the funds asset portfolio in the analyzed countries, from 1995 to 2004, observing the macroeconomic context on the analyzed period.